Understanding the determinants of users’ continuance intention to buy low-cost airline flights online - Tam, Carlos (2022)
TTam, C., Barroso, M., & Cruz-jesus, F. (2022). Understanding the determinants of users’ continuance intention to buy low-cost airline flights online. Journal of Hospitality and Tourism Technology, 13(2), 264-280. https://doi.org/10.1108/JHTT-12-2020-0316